Knowledge Assimilation at Foreign Subsidiaries of Japanese MNCs through Political Sensegiving and Sensemaking. Issue 9 (September 2016) - Hong, Jacky F. L.; Snell, Robin Stanley; Mak, Carry
We analyse political sensegiving and sensemaking by expatriates and host country employees through exportive, contestative and integrative stages of knowledge assimilation at two China-based subsidiaries of different Japanese MNCs. Comparative case study analysis indicated that efforts by expatriates and HQ-based experts to convey, routinize and standardize home country practices during the exportive and contestative stages, while involving traditional 'one way' knowledge transfer, can provide a foundation for a subsequent integrative stage, during which host country employees' locally embedded knowledge is assimilated despite geopolitical asymmetry between home and host countries. Without this foundation, knowledge assimilation can remain 'frozen' at the contestative stage, with host country employees resisting importation of good practices from the HQ, and expatriates marginalizing host country employees' contributions unless these are exceptionally compelling.